2020
DOI: 10.1186/s12873-020-00348-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of post-traumatic stress disorder among road traffic accident survivors: a prospective survey at selected hospitals in southern Ethiopia

Abstract: Background: Post-traumatic stress disorder (PTSD) is prevalent among road traffic accident survivors (RTA), yet the psychological welfare of the persons has largely been ignored as health care professionals focus more on managing physical injuries. Many literatures from other parts of the world have addressed the issue of posttraumatic stress disorder among road traffic accident survivors, but such studies are mostly unavailable in sub-Saharan Africa, especially in Ethiopia. Therefore, this study examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 35 publications
6
32
1
1
Order By: Relevance
“…We also found that pre-MVC histories were strong predictors of the 3-month outcome. This is broadly consistent with previous research showing that histories of PTSD (Beliveau et al, 2019;Breslau et al, 2008;Kessler et al, 2018) and more general psychopathology (Bedaso et al, 2020;Heron-Delaney et al, 2013) strongly predict posttraumatic adjustment. We also found that these associations were mediated by 2-and 8-week disorders and that significant interaction existed between pre-MVC histories and the mediators due to pre-MVC histories predicting onset and persistence of these intervening disorders as well as the higher conditional prevalence of the 3-month outcome in the presence of these intervening disorders.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found that pre-MVC histories were strong predictors of the 3-month outcome. This is broadly consistent with previous research showing that histories of PTSD (Beliveau et al, 2019;Breslau et al, 2008;Kessler et al, 2018) and more general psychopathology (Bedaso et al, 2020;Heron-Delaney et al, 2013) strongly predict posttraumatic adjustment. We also found that these associations were mediated by 2-and 8-week disorders and that significant interaction existed between pre-MVC histories and the mediators due to pre-MVC histories predicting onset and persistence of these intervening disorders as well as the higher conditional prevalence of the 3-month outcome in the presence of these intervening disorders.…”
Section: Discussionsupporting
confidence: 91%
“…Although it is known that prior history of posttraumatic stress disorder (PTSD; Beliveau et al, 2019; Breslau et al, 2008; Kessler et al, 2018) and major depressive episode (MDE; Bedaso et al, 2020; Heron‐Delaney et al, 2013) both strongly predict adjustment after subsequent traumas (Ikin et al, 2010; Pozzato et al, 2020) and are highly comorbid (Kenardy et al, 2018), a better understanding of these associations is needed to inform early intervention targeting. Are these histories important because they are associated with peritraumatic symptoms that can be assessed in the immediate aftermath of a subsequent trauma?…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of PTSD in the present study was lower than studies conducted in Ethiopia,[ 17 ]22.8%; southeastern Nigeria,[ 22 ]26.7%; Australia,[ 23 ]19.3%; southern Ethiopia,[ 24 ]15.4%; and Zurich,[ 25 ]4.7%. This varied prevalence of PTSD could be explained by different time points of PTSD assessment, different sample sizes, and cultural and socioeconomic status among the study population.…”
Section: Discussioncontrasting
confidence: 82%
“…17 PTSD could result in long-term adverse consequences if left untreated, mainly it leads to social and functional impairments in survivors of conflict. 18 According to meta-analysis conducted on a global population of adult war survivors that reviewed all countries that suffered at least one war within their own territory between 1989 and 2015 found that 23.81% of adult war survivors met diagnostic criteria for PTSD. 6 A community-based cross-sectional study done in Nepal reported the prevalence of posttraumatic disorder to be 9.6%.…”
Section: Introductionmentioning
confidence: 99%